2006
DOI: 10.1074/jbc.m605003200
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Features in the Extracellular Domain of Human Toll-like Receptor 8 Are Essential for pH-dependent Signaling

Abstract: Toll-like receptor (TLR) 8 has an important role in initiating immune responses to viral single-stranded RNA and the antiviral compound resiquimod. Together with TLR3, -7, and -9, it forms a subgroup of the TLRs that are localized intracellularly and signal in response to pathogen-derived nucleic acids. In this work, we have used site-directed mutagenesis to identify regions of the TLR8 extracellular domain that are required for stimulusinduced signal transduction. We have shown that a cysteinerich sequence pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
54
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 29 publications
6
54
0
Order By: Relevance
“…Furthermore, the previous demonstration that transient overexpression of hTLR8 in HEK293 and U20S cells reconstitutes responsiveness to ssRNAs via activation of NF-B (11,31) indicates that hTLR8 does not require hTLR7 for signaling when expressed artificially. The discrepancies between these results and the data presented here are likely related to overexpression of TLRs in these studies and the saturation doses of ssRNAs used (ϳ3-fold higher than the highest dose used here).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the previous demonstration that transient overexpression of hTLR8 in HEK293 and U20S cells reconstitutes responsiveness to ssRNAs via activation of NF-B (11,31) indicates that hTLR8 does not require hTLR7 for signaling when expressed artificially. The discrepancies between these results and the data presented here are likely related to overexpression of TLRs in these studies and the saturation doses of ssRNAs used (ϳ3-fold higher than the highest dose used here).…”
Section: Discussionmentioning
confidence: 99%
“…Structural analysis of TLR8 will probably result in more information of a potential ligand binding site and further help to explain functional differences among vertebrates. Initial mutagenesis studies identified regions in the human TLR8 extracellular domain most probably involved in signaling (48). Specific residues in LRR8 and LRR17 appear to be absolutely required for human TLR8 activation (48), and mutation of a residue in LRR17 of human TLR9 abolished specific binding to CpG DNA (30), indicating a role for LRR17 in ligand recognition for TLR7, 8, and 9 due to the similarities between these TLRs.…”
Section: Discussionmentioning
confidence: 99%
“…Initial mutagenesis studies identified regions in the human TLR8 extracellular domain most probably involved in signaling (48). Specific residues in LRR8 and LRR17 appear to be absolutely required for human TLR8 activation (48), and mutation of a residue in LRR17 of human TLR9 abolished specific binding to CpG DNA (30), indicating a role for LRR17 in ligand recognition for TLR7, 8, and 9 due to the similarities between these TLRs. Unfortunately, nothing is known yet about the potential function of LRR3, but our data suggest that this region plays a role in species-specific recognition of RNA by TLR8.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that DNA binding and responsiveness are distinct events and that intrinsic structural differences between mammalian TLR9 contribute to the species-specific response to ODNs. Recent evidence shows that fulllength TLR9 (i.e., not the TLR chimeric protein) targeted to the cell surface using a yeast sorting sequence is unresponsive, and that the receptor requires a low pH (31) and protease activity (12) in the endolysosomes to gain functionality. As the uptake of CpG DNA via endocytosis is not DNA sequence specific (4), these results suggest that the physical properties of the (polyanionic) ligand at low pH (35), possible regulatory molecules (39), and/or intracellular processing of TLR9 (11,12) are important for the species-specific response to CpG DNA (7).…”
Section: Discussionmentioning
confidence: 99%